Neonatal Sepsis in a Tertiary Care Hospital: Bacteriological Profile, Antibiotic Sensitivity Pattern and Outcome - Pranav Prakash Rai; Atul Goel; Baljeet Maini; Bablu Kumar Gaur; Umar Farooq (JCDR Research and Publications Pvt. Ltd., 2020)
Introduction: Neonatal septicaemia refers to generalised bacterial infection confirmed by positive blood culture in the first 28 days of life and it is a leading cause of morbidity and mortality in the Neonatal Intensive Care Units (NICU) of India. Aim: To isolate and identify the bacterial agents responsible for neonatal sepsis and to determine the antibiotic sensitivity patterns of isolates in a tertiary care hospital in Uttar Pradesh. Materials and Methods: A total of 132 neonates (0 to 28 days) admitted to NICU with a diagnosis of probable sepsis were included. Informed consent obtained from their parents. Detailed history, general physical examination, demographics data, neonatal risk factors, and lab data including sepsis screen bacterial growth and antibiotic sensitivities patterns were studied and analysed. Results were analysed using MS Excel and group comparisons were done by applying chisquare test. Results: Blood culture reports were positive in 57 (43.2%) neonates. In culture proven sepsis, 34 (59.6%) neonates had Early Onset Neonatal Sepsis (EONS) and 23 (40.4%) had Late Onset Neonatal Sepsis (LONS). Common clinical presentation of neonatal sepsis was breathing difficulty and refusal to feed. Most common maternal risk factor was prolonged rupture of membrane (>24 hours). Low birth weight and prematurity were important neonatal risk factors for sepsis. The most frequently isolated organisms in blood were gram negative bacteria (Acinetobacter baumanii21.1% and Klebsiella pneumoniae- 17.5%). Most of isolates showed high resistance to commonly used antibiotics such as penicillin/ampicillin, cefotaxime and amikacin. Conclusion: Gram negative organisms were the most common cause of neonatal sepsis and majority of isolates were resistant to commonly prescribed antibiotics, which present a great threat to newborn survival, and thereby require rational antibiotic policy for NICU.